Perbandingan Perolehan Bahasa Inggris di Indonesia, Thailand dan Philipina - Ima Widyastuti; Nanang Bagus Subekti; Victa Sari Dwi Kurniati; Diona Emelza Kaban; Topan Gilang Sagita (WACANA AKADEMIKA: Majalah Ilmiah Kependidikan, 2021)
International cooperation between universities is one of the strategic issues for the internationalization of a university in Indonesia. One form of cooperation is not only manifested in the tri dharma aspect of higher education. The focus of this research is the comparison of students' mastery of English in the three countries. This English language ability aims to determine the ability of students who take part in student exchange programs or internship exchange programs conducted by three universities. This descriptive qualitative research involved students from universities in Indonesia, universities in Thailand, and the Philippines. Data taken from interviews with several English learners were then transcribed, coded, and analyzed to determine the stage of mastery of English according to Processability Theory. The results of this study indicate that although there are differences in the use of English in the three countries, participants from the three countries have the same attainment of mastery of English. Participants in the Philippines were more active in using English, considering that English in this country is a second language. Unlike Thailand and Indonesia, which place English as a foreign language. However, the highest mastery of English achieved by participants in the three countries was the same, namely at Stage 3 in Processability Theory.